Copper‐Promoted Sandmeyer Difluoromethylthiolation of Aryl and Heteroaryl Diazonium Salts1. Issue 26 (12th May 2015) - Wu, Jiang; Gu, Yang; Leng, Xuebing; Shen, Qilong
Abstract An efficient copper‐promoted difluoromethylthiolation of aryl and heteroaryl diazonium salts is described. The reaction is conducted under mild reaction conditions and various functional groups were compatible. In addition, reactions of heteroaryl diazonium salts such as pyridyl, quinolinyl, benzothiazolyl, thiophenyl, carbazolyl, and pyrazolyl diazonium salts occurred smoothly to afford the medicinally important difluoromethylthiolated heteroarenes. Furthermore, a more practical one‐pot direct diazotization and difluoromethylthiolation protocol was developed, and it converts the aniline derivatives into difluoromethylthiolated arenes. The utility of the method is demonstrated by difluoromethylthiolation of a number of natural products and drug molecules.